Storing up trouble - Turano, Jen (Turano, Jen. American heiresses, 2020)
"In 1886, Beatrix Waterbury's train is disrupted by a heist, scientist Norman Nesbit comes to her aid. He's swept up in the havoc she always seems to attract-including the attention of the men trying to steal his research - and they discover the curious way feelings can grow despite chaos"--Provided by publisher.